2016
DOI: 10.3354/meps11575
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in stable isotopic and fatty acid composition of anguilliform leptocephali and particulate organic matter in the South Pacific

Abstract: The feeding ecology of leptocephali has remained poorly understood because they apparently feed on particulate organic matter (POM), which varies in composition, and it is unclear which components of the POM they assimilate. The δ13C and δ15N stable isotope (SI) and fatty acid (FA) compositions of 3 families of leptocephali and POM were compared in 3 latitudinal current zones of the western South Pacific. The δ15N signatures of leptocephali and POM overlapped, with both having their lowest values in the southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 79 publications
(142 reference statements)
0
32
0
Order By: Relevance
“…In addition, a DNA barcoding study on small European eel larvae found that sequences were present from a wide range of organisms ), which appears to be consistent with what would be expected to be found in marine snow that contains many types of organismal and other materials (Alldredge and Silver 1988;Holloway and Cowen 1997;Shanks and Walters 1997;Kiørboe 2000). Stable isotope studies indicate that leptocephali probably do not consume all types of POM or do not assimilate everything they consume (such as fecal pellets), and their isotopic signatures and trophic position are not consistent with feeding on other food sources such as zooplankton (Miller et al 2013a;Feunteun et al 2015;Liénart et al 2016).…”
Section: Biology and Ecology Of Anguillid Leptocephalimentioning
confidence: 54%
“…In addition, a DNA barcoding study on small European eel larvae found that sequences were present from a wide range of organisms ), which appears to be consistent with what would be expected to be found in marine snow that contains many types of organismal and other materials (Alldredge and Silver 1988;Holloway and Cowen 1997;Shanks and Walters 1997;Kiørboe 2000). Stable isotope studies indicate that leptocephali probably do not consume all types of POM or do not assimilate everything they consume (such as fecal pellets), and their isotopic signatures and trophic position are not consistent with feeding on other food sources such as zooplankton (Miller et al 2013a;Feunteun et al 2015;Liénart et al 2016).…”
Section: Biology and Ecology Of Anguillid Leptocephalimentioning
confidence: 54%
“…Isotopic variation was evident among leptocephali collected in the GOM and off NC. This variation could be driven by differences in the baseline POM, as well as regional variability in the nutritional quality of POM assimilated by leptocephali (Lienart et al ). The δ 13 C values (−26 to −18‰) of leptocephali collected in the GOM were comparable to coastal GOM larval fish species that derive their carbon from phytoplankton (Thayer et al , ), thus supporting a diet consisting of material at or near the base of the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Feunteun et al () noted that leptocephali in the western Indian Ocean might feed on different POM components depending on region, depth and season. In the South Pacific Ocean, Lienart et al () reported geographic differences in both POM and leptocephali. An alternative explanation for differences in δ 13 C values may be due to different assimilation times of food or leptocephali assimilating POM differently (Lienart et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations